Reversal Role Suami-Istri dan Dampaknya Terhadap Perceraian Perspektif Normatif Yuridis : - Rohmah, Lutfatur; Mustahal, Muhamad; Abqori, Najih (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research explores the occurrence of role reversal between husband and wife and the effects it has on divorce from a normative-juridical perspective using a feminist approach and gender studies. The case study was conducted on the couple Rina and Dedi, who live in Erorejo Village, Wadaslintang District, Wonosobo Regency, using original data gathered from detailed interviews. Theoretically, this research is based on sociological theory, particularly structural-functionalism, as well as normative legal analysis of marriage regulations in Indonesia. The results show that changes in gender roles, where the wife becomes the primary breadwinner while the husband handles domestic work, trigger social dysfunction and a masculine identity crisis in the husband, which then gives rise to emotional conflict and tension in power relations within the family. Despite these changes in roles within the household, patriarchal values ​​in legal and social norms remain deeply rooted, creating tensions that lead to infidelity and divorce. From a normative-juridical perspective, the divorce is declared valid in accordance with applicable legal provisions. However, national marriage law is considered insufficiently flexible to accommodate changes in gender roles in society. The feminist approach in this study highlights the significance of a family law system that is more equal and flexible reforms to current social dynamics, to advance fairness and equal rights marital relationships.